Antiquity and Its Reception Modern Expressions of the Past - Trindade Lopes, Helena; Gomes de Almeida, Isabel; de Fátima Rosa, Maria (IntechOpen, 2020)
What do we talk about when we talk about antiquity? For the majority of the population, the term immediately transports us to the notion of an ancient age or ancient world (the Parthenon, Athens, and the Coliseum of Rome), which condenses in itself the Greco-Roman world. This reduces antiquity to antiquity that was structurally essential for the construction and emergence of the civilization called occidental.For others, because of their religious backgrounds, antiquity goes back in time and enlarges, in part, its space of action, allowing the emergence of Palestine as a primordial territory.But these two visions (old and supported by a scientific ignorance of the ancient geographies and chronologies) enclose the history in a limited time and space. As if there would never have been a world before that time. As if the civilization that we comfortably call ourselves as inheritors, the so-called "Occidental Civilization" was the first step in the history of man on earth.